The relationship between cyber loafing and task performance at Lembaga Kenaf dan Tembakau Negara, Kubang Kerian, Kelantan / Siti Nor Anisah Abdul Rahman - Abdul Rahman, Siti Nor Anisah (2014)
Research has found that cyber loafing have the relationship with the task performance. Contributing to significant business opportunities and the enhancement of employee's productivity, the Internet has changed how work is done. These benefits, including cost reductions, decreased product cycle time, and easier access to information are not without a downside. The use of the Internet in the workplace has also raised concerns regarding privacy, organizational liability and a new workplace threat to productivity - Cyber loafing, as a result of employees non-work related internet activities. This study reports the relationship between Cyber loafing and Task Performance among employees at Lembaga Kenaf and Tembakau Negara, Kelantan. The purpose of this investigation was to identify what are the factors that lead to employees cyber loafing at Lembaga Kenaf dan Tembakau Negara, Kelantan and to identify the consequences of cyber loafing to task performance.